2017
DOI: 10.1021/jacs.6b13171
|View full text |Cite
|
Sign up to set email alerts
|

C–I···π Halogen Bonding Driven Supramolecular Helix of Bilateral N-Amidothioureas Bearing β-Turns

Abstract: We report the first example of C-I···π halogen bonding driven supramolecular helix in highly dilute solution of micromolar concentration, using alanine based bilateral I-substituted N-amidothioureas that contain helical fragments, the β-turn structures. The halogen bonding interactions afford head-to-tail linkages that help to propagate the helicity of the helical fragments. In support of this action of the halogen bonding, chiral amplification was observed in the supramolecular helix formed in acetonitrile so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
97
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 54 publications
0
97
0
2
Order By: Relevance
“…These dimers are further linked tail-to-head between alkyl segments via van der Waals force to give 1D zig-zag packing.T he 1D packing arrays along the b axis adopt a P-type handedness from the amplification of intrinsic molecular chirality of cholesterol domains. [26,27] Most of integrated WAXS peaks for 2aand 2ccould be assigned according to the comparison with simulated XRD patterns (Supporting Information, Figures S13 and S14), revealing ag ood agreement between their crystal structures and self-assemblies in decane.…”
Section: Angewandte Chemiementioning
confidence: 91%
“…These dimers are further linked tail-to-head between alkyl segments via van der Waals force to give 1D zig-zag packing.T he 1D packing arrays along the b axis adopt a P-type handedness from the amplification of intrinsic molecular chirality of cholesterol domains. [26,27] Most of integrated WAXS peaks for 2aand 2ccould be assigned according to the comparison with simulated XRD patterns (Supporting Information, Figures S13 and S14), revealing ag ood agreement between their crystal structures and self-assemblies in decane.…”
Section: Angewandte Chemiementioning
confidence: 91%
“…. π interactions, while other inter-helices XBs create a complex network [93]. Substituting iodine with chloride, helical structures do not form in the solid state.…”
Section: Nuclear Overhauser Effectmentioning
confidence: 99%
“…An X-ray of the crystal structure demonstrated that the monomer self-organizes in supramolecular helices held together by iodine…π interactions, while other inter-helices XBs create a complex network [93]. Substituting iodine with chloride, helical structures do not form in the solid state.…”
Section: Nuclear Overhauser Effectmentioning
confidence: 99%
“…X-ray crystal structure demonstrated that the monomer self-organizes in supramolecular helices held together by iodine … π interactions, while other inter-helices XBs create a complex network. [54] Substituting iodine with chloride, helical structures do not form in the solid state. Comparing X-ray structures with NOESY spectra, the authors deduced that when X = Cl (LL-ACl), only intramolecular NOE contacts are visible and, in particular, the e-f contact is well visible (internuclear e-f distance in the solid-state structure: 3.189 Å) and the e-g is not (internuclear e-g distance in the solid-state structure: 4.348 Å, Figure 8).…”
Section: Nuclear Overhauser Effectmentioning
confidence: 99%